Spatial Localization and Quantitation of Androgens in Mouse Testis by Mass Spectrometry Imaging - Cobice, Diego F; Livingstone, Dawn E W; Mackay, C Logan; Goodwin, Richard J A; Smith, Lee B; Walker, Brian R; Andrew, Ruth (Analytical chemistry (Washington), 2016)
Androgens are essential for male development and reproductive function. They are transported to their site of action as blood-borne endocrine hormones but can also be produced within tissues to act in intracrine and paracrine fashions. Because of this, circulating concentrations may not accurately reflect the androgenic influence within specific tissue microenvironments. Mass spectrometry imaging permits regional analysis of small molecular species directly from tissue surfaces. However, due to poor ionization and localized ion suppression, steroid hormones are difficult to detect. Here, derivatization with Girard T reagent was used to charge-tag testosterone and 5α-dihydrotestosterone allowing direct detection of these steroids in mouse testes, in both basal and maximally stimulated states, and in rat prostate. Limits of detection were ∼0.1 pg for testosterone. Exemplary detection of endogenous steroids was achieved by matrix-assisted laser desorption ionization and either Fourier transform ion cyclotron resonance detection (at 150 μm spatial resolution) or quadrupole-time-of-flight detection (at 50 μm spatial resolution). Structural confirmation was achieved by collision induced fragmentation following liquid extraction surface analysis and electrospray ionization. This application broadens the scope for derivatization strategies on tissue surfaces to elucidate local endocrine signaling in health and disease.